Frequency of Human Papillomavirus Detection in Chagasic Megaesophagus Associated or Not with Esophageal Squamous Cell Carcinoma - Munari, Fernanda Franco; Sichero, Laura; Carloni, Adriana Cruvinel; Lacerda, Croider Franco; Nunes, Emily Montosa; De Oliveira, Antônio Talvane Torres; Scapulatempo-Neto, Cristovam; Da Silva, Sandra Regina Morini; Crema, Eduardo; Adad, Sheila Jorge [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP]; Henry, Maria Aparecida Coelho Arruda [UNESP]; et al. (Karger Publishers, 2022)
Background: Chagasic megaesophagus (CM) as well as the presence of human papillomavirus (HPV) has been reported as etiological factors for esophageal squamous cell carcinoma (ESCC). Objective: We assessed the prevalence of HPV DNA in a series of ESCCs associated or not with CM. Data obtained were further correlated to the pathological and clinical data of affected individuals. Methods: A retrospective study was performed on 92 formalin-fixed and paraffin-embedded tissues collected from patients referred to 3 different hospitals in São Paulo, Brazil: Barretos Cancer Hospital, Barretos, São Paulo; Federal University of Triângulo Mineiro, Uberaba, Minas Gerais; and São Paulo State University, Botucatu, São Paulo. Cases were divided into 3 groups: (i) 24 patients with CM associated with ESCC (CM/ESCC); (ii) 37 patients with ESCC without CM (ESCC); and (iii) 31 patients with CM without ESCC (CM). Detection of HPV DNA was assessed in all samples by a genotyping assay combining multiplex polymerase chain reaction and bead-based Luminex technology. Results: We identified a high prevalence of high-risk HPV in patients in the CM group (12/31, 38.8%) and CM/ESCC (8/24, 33.3%), compared to individuals in the ESCC group (6/37, 16.3%). The individuals in the groups with cancer (ESCC and CM/ESCC) had a higher frequency of HPV-16 (4/9, 44.5% and 2/8, 25.0%). The other types of high-risk HPVs detected were HPV-31, 45, 51, 53, 56, 66, and 73. We also observed in some samples HPV coinfection by more than one viral type. Despite the high incidence of HPV, it did not show any association with the patient's clinical-pathological and molecular (TP53 mutation status) characteristics. Conclusion: This is the first report of the presence of HPV DNA in CM associated with ESCC. HPV infection was more presence in megaesophagus lesions. Further studies are needed to confirm and better understand the role of persistent HPV infection in patients with CM.
Keywords: Brazil; Chagas disease; Chagasic megaesophagus; Esophageal cancer; Esophageal squamous cell carcinoma; Human papillomavirus